2023
DOI: 10.1177/1420326x231153924
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for phase change material integration in building components

Abstract: With the recent dramatic growth of the building sector’s energy consumption to provide thermal comfort to consumers, the constraints of climate change and the scarcity of energy supplies have necessitated a wiser and more effective reduction in the amount consumed. As a result, phase change materials (PCMs) have attracted much interest as latent heat thermal storage systems in recent decades. This paper aims to explain the possibility of using PCMs in buildings by establishing an overall conceptual framework f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…In addition, positive relationships could be observed by the solar collector s width and each floor s airflow rate. Moreover, the solar chimney design can be optimized to provide the indoor air velocity and thermal comfort, as indicated in [25], where they highlighted that the most important factor is the width of the solar…”
Section: Various Configuration Parameters Related To Sc Performance-d...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, positive relationships could be observed by the solar collector s width and each floor s airflow rate. Moreover, the solar chimney design can be optimized to provide the indoor air velocity and thermal comfort, as indicated in [25], where they highlighted that the most important factor is the width of the solar…”
Section: Various Configuration Parameters Related To Sc Performance-d...mentioning
confidence: 99%
“…Numerous computational, analytical, and experimental studies for multi-zone and zonal models as well as for small-scale and full-scale experimental prototypes have shown that the chimney's shape and morphology affect the flow rate and ACH [15,25,46,50,55,57,[70][71][72][73][74]. Patel SK, Prasad D, and Ahmed MR [46] explored the influence of various geometric parameters on a SCPP such as the collector inlet opening and the collector outlet.…”
Section: Various Configuration Parameters Related To Sc Performance-d...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, extensive research has focused on innovative insulation alternatives, with the use of phase change materials (PCMs) standing out as a promising solution for regulating indoor temperatures [7,8]. Encapsulating PCMs within structural materials has emerged as an effective approach to enhance building energy efficiency and reduce overall energy consumption [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, at nighttime, the PCMs solidify and release stored heat, contributing to natural insulation and potentially reducing the need for heating [14]. Integrating PCMs as a thermal regulation strategy offers multiple benefits, including increased energy efficiency by managing temperature imbalances, enhanced occupant comfort by creating a stable indoor environment, and environmental sustainability through reduced greenhouse gas emissions associated with traditional heating and cooling systems [8].…”
Section: Introductionmentioning
confidence: 99%